Mary Ellen Avery’s Research Career – Remembrance of Things Past - Torday, John Steven (Frontiers in Pediatrics, 2014)
Mary Ellen Avery’s research is recognized as a milestone in biomedical research. She had discovered the underlying cause of Hyaline Membrane Disease, surfactant deficiency, fostering ever more vigorous efforts to reduce neonatal mortality in the burgeoning practice of Neonatology. Neonatology is the only clinical discipline that began as an experiment, making it a model for biomedical research. Avery knew that the concerted effort to treat preterm newborns could potentially do more harm than good, violating her oath to Hippocrates, if not held to the highest scientific standards. She remained true to that pledge throughout her career, as recounted in this Review.